2019
DOI: 10.1093/jpe/rtz036
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nitrogen deposition on terrestrial plant diversity: a meta-analysis in China

Abstract: Aims With the global atmospheric nitrogen (N) deposition increasing, the effect of N deposition on terrestrial plant diversity has been widely studied. Some studies have reviewed the effects of N deposition on plant species diversity; however, all studies addressed the effects of N deposition on plant community focused on species richness in specific ecosystem. There is a need for a systematic meta-analysis covering multiple dimensions of plant diversity in multiple climate zones and ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Although elevated N and P could promote plant productivity as most natural terrestrial land areas are N and P limited (Du et al, 2020), soil N and P loadings threaten biodiversity and ecosystem functions important to human well-being (Tilman & Lehman, 2001). Plant diversity and plant community stability have been shown to decline with N (Han et al, 2019;Isbell et al, 2013;Reich, 2009;Simkin et al, 2016) and P accumulation (Ceulemans et al, 2014;Gilbert et al, 2009). Diversity loss in response to nutrient enrichment is often accompanied by changes in species composition, with native and perennial grassland species frequently showing greater vulnerability to decline than non-native or annual species (Avolio et al, 2014;Bai et al, 2010;Clark & Tilman, 2008;Flores-Moreno et al, 2016;Foster et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although elevated N and P could promote plant productivity as most natural terrestrial land areas are N and P limited (Du et al, 2020), soil N and P loadings threaten biodiversity and ecosystem functions important to human well-being (Tilman & Lehman, 2001). Plant diversity and plant community stability have been shown to decline with N (Han et al, 2019;Isbell et al, 2013;Reich, 2009;Simkin et al, 2016) and P accumulation (Ceulemans et al, 2014;Gilbert et al, 2009). Diversity loss in response to nutrient enrichment is often accompanied by changes in species composition, with native and perennial grassland species frequently showing greater vulnerability to decline than non-native or annual species (Avolio et al, 2014;Bai et al, 2010;Clark & Tilman, 2008;Flores-Moreno et al, 2016;Foster et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient addition results in increased aboveground biomass, and subsequent aboveground competition for light changes the plant community and results in reduced species richness (Suding et al ., 2005; Hautier et al ., 2009; Borer et al ., 2014). In addition, nutrient addition also may reduce plant diversity through soil acidification, ammonium toxicity, altered plant–soil relationships, and increased sensitivity to secondary stress such as pests and drought and other disturbances (Soons et al ., 2017; Han et al ., 2019; Midolo et al ., 2019). However, responses of AMF to nutrient enrichment are highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…In an old-growth subtropical forest in southern China, N additions of greater than 100 kg N ha −1 yr −1 decreased the abundance of understory seedlings, ferns and mosses, but did not affect canopy trees and shrubs [116]. A recent meta-analysis of experimental results in China concluded that N addition negatively affected plant biodiversity in grasslands and forest understory communities; the effects varied by climatic zone, N addition level and duration [117]. However, there are relatively few reports from eastern and southern China [117], where high-level N deposition has occurred for decades.…”
Section: Atmospheric N Deposition and Ecological Impactsmentioning
confidence: 99%
“…A recent meta-analysis of experimental results in China concluded that N addition negatively affected plant biodiversity in grasslands and forest understory communities; the effects varied by climatic zone, N addition level and duration [117]. However, there are relatively few reports from eastern and southern China [117], where high-level N deposition has occurred for decades. In these regions, N addition experiments likely underestimate the negative effects because high-level N deposition may have already caused a shift in plant species composition towards that better adapted to high N availability before the experiments began.…”
Section: Atmospheric N Deposition and Ecological Impactsmentioning
confidence: 99%